THE RELATIONSHIP BETWEEN MOTHER AND PREMATURE BABY AFTER ADMISSION TO HOSPITAL - Gécica Gracieli Wust; Cláudia Silveira Viera (Universidade Federal do Paraná, 2011)
This study had as its aim to describe the mother-premature baby relationship after discharge from a neonatal intensive therapy unit, considering that both pass through deprivation of contact after the birth. It is characterized by qualitative research, of case-study type. The study subjects were four mothers whose children were hospitalized between October and December 2008. The data were collected via interviews during home visits in the first week after hospital discharge; the precepts of thematic analysis were used for the analysis. From the study it emerged that the mother-child relationship can be understood from three angles: being together at home; the change in the family dynamics due to the baby's arrival; and caring for the new-born at home. Being familiar with the mother-child interactions after hospital discharge provides means of caring while contributing to the cognitive, affective and social development of the baby, and helps the mother to develop her maternal abilities.